Entre rótulos e identidades: o estigma dos jovens infratores na socioeducação - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This study examines how stigma associated with youth offenders affects their educational process within the juvenile justice educational programs of the Federal District, Brazil. Grounded in Morin's complexity theory and dialogical principle, the research integrates critical criminology and symbolic interactionism, providing a comprehensive theoretical lens. Employing a mixed methodology, the investigation combines documentary analysis with an in-depth ethnographic approach. The study was conducted in three distinct juvenile detention facilities: the Santa Maria Detention Center (UISM), the Recanto das Emas Detention Center (UNIRE), and the Gama Female Detention Center (UIFG). Initially, legislation pertaining to the Brazilian juvenile justice system was analyzed. Subsequently, focus groups were held with youth in custody, critically informed by Erving Goffman's seminal literature on stigma. Drawing on Goffman's theoretical concepts of "presentation of self" and "total institution," the study explores how adolescents manage their identities and develop adaptation and resistance strategies within these highly controlled environments. The results indicate that juvenile justice institutions exert pervasive control over all aspects of the residents' lives through intricate systems of rules, privileges, and punishments, which profoundly shape behaviors and identities. The research concludes that the stigma intrinsically linked to the label of "juvenile offenders" significantly compromises the educational process within the juvenile justice system. This stigma acts as a structural obstacle, impeding the effective implementation of the pedagogical dimension of juvenile justice measures and limiting opportunities for identity reconstruction and successful social reintegration of these adolescents.
Between labels and identities: the stigma of young offenders in juvenile justice educational programs
Keywords: Adolescentes – Conflito com a lei; Medidas socioeducativas; Jovem infrator – Estigma; Criminologia crítica; Interacionismo simbólico; Youth offenders; Juvenile justice educational programs; Young offender - Stigma; Critical criminology; Symbolic interactionism; CIENCIAS HUMANAS::EDUCACAO; FUNDAMENTOS DA EDUCACAO::SOCIOLOGIA DA EDUCACAO